Clearance of Renal Stone in PCNL Under Spinal Anaesthesia (Bangladesh Journal of Urology, 2020)
Objective: To evaluate the Outcome of PCNL under spinal Anaesthesia.Material and Method: A total of 74 patients with renal stone disease were treated by PCNL under spinal anasthesia. Total study period was from January 2013 to October 2019. Pre operative and post operative variables and complications were recorded.Result: Age range from 25 years to 65 years, mean 41.37 ± 33 yrs. Male female ratio was 6.4:1 stone size ranges from 15mm to 40mm, majority was 21.33mm. Mean operative time was 69±4.2 min. Total stone clearance was 15.60%. Only 10.82% patients were suffering from grade I complications and mean hospital stay was 3.1±0.6 days.Conclusion: Percutaneous nephrolithotomy is effective and safe under spinal anesthesia with shorter hospital stay and minimal complication.Bangladesh Journal of Urology, Vol. 23, No. 2, July 2020 p.154-157